PENINGKATAN KETERAMPILAN TATA BOGA MELALUI MEDIA VIDEO PADA ANAK TUNAGRAHITA RINGAN DI KELAS VII SMPLB ANAK BRILIANT BATAM TAHUN PELAJARAN 2019/2020 - Fitria Meilina; Dormauli Sitanggang; Fadli Surahman (Universitas Karimun Prodi S1 Pendidikan Luar Biasa, 2021)
The research is motivated by the learning process teacher centered and low score from learning process of student. This study aim to improve culinary learning process in recognizing tools, ingredients and making bakwan. This type of research classroom action research. The sample in this study was a grade 7 SMPLB Anak Briliant Batam, that consisted of 9 students. Data collection technigues using observation, documentation and test result. Data analysis techniques were obtained from teacher assessment data analysis, student assessment data analysis and Learning Outcomes data analysis. The result in this study were increased from the beginning of learning to get an average value 60,77%, cycle I average value of 74,77% and cycle II average value 86%. The conclusion of this study is an increase in the use of video media for culinary learning outcomes in the subject matter of recognizing tools, materials and making bakwan.